RESISTANCE OF SOME NEW CLONES OF EUCALYPTUS TO INSECTS CAUSES GALL IN MOUNT MUTIS, NTT - Safitri, Betari; Hidayat, Purnama; Buchori, Damayanti (Universitas Lampung, 2019)
Eucalyptus (Eucalyptus spp.) is a fast-growing tree native in Australia, Papua, and Eastern part of Indonesia. It is valued for its timber, oil, gum, and resin, and as an ornamental tree. Many eucalyptus clones have been developed and planted for timber production in Sumatera. Several galls caused by insects are known as serious pests of eucalyptus and can reduce the quality and quantity of the timber production. This study was aimed to identify the gall inducers and describe the galls that formed on the eucalyptus clones which planted in Mt. Mutis, East Nusa Tenggara Province. The research was conducted from October 2017 to July 2018. A total of 855 seedlings consisting of 57 clones and 15 plants for each clone were planted in Mt. Mutis. Observations of the gall symptoms were done biweekly on each plant. Gall symptoms were directly observed and identified, included the form, size, location, color, and insect that caused the gall. There were four types of gall forms were recorded. One type of gall caused by Ophelimus sp. (Hymenoptera: Eulophidae) which similar to the gall recorded in Sumatera and Java. The other three gall forms were never been reported in Indonesia. The insects that associated with galls were Hymenoptera and Diptera orders. The type of gall that mostly found in the eucalyptus clones was the big clustered leaf gall caused by Fergusonina sp. (Diptera:Ã‚Â Fergusoninidae).Ã‚Â There are only two clones which are included as susceptible clones based on the type of gall formed, C35 and C53. There were 27 eucalyptus clones with no gall infestations which were considered as the good candidate of resistance eucalyptus clones to the gall infestations.